Application of Specialized Linguistic Knowledge in Legal Proceedings: Differentiation and Integration - Vitaly O. Kuznetsov (Теория и практика судебной экспертизы)
The article addresses the influence of multidirectional processes of differentiation and integration of specialized linguistic knowledge on the development of forensic science and the practice of expert research, where it is used. The author highlights that both processes contribute to developing theoretical and methodological provisions that allow experts to solve new and complex problems at a higher quality level. The role of differentiation of specialized linguistic knowledge is to create new kinds and types of forensic examinations: author’s, linguistic, forensic analysis of video and sound recordings, forensic research of intellectual property objects. At the same time, the integration of specialized linguistic knowledge ensures the development of the whole scientific direction.